A Cross-Layer Design Combining of AMC with HARQ for DSRC Systems. (17th November 2013) - Zhang, Gao Yuan; Sun, Li Min; Wen, Hong; Wu, Bin; Zhu, Xiping; Zhou, Liang
Abstract : A new cross-layer design combining adaptive modulation and coding (AMC) with Hybrid Automatic Repeat Qequest (HARQ) based on rate-compatible LDPC codes is proposed for IEEE Std. 802.11p in DSRC systems. Instead of considering AMC at the physical layer and ARQ at the data link layer separately, we propose a cross-layer design that combines these two layers judiciously to maximize either spectral efficiency or throughput. With ARQ correcting occasional packet errors at the data link layer, the stringent error control requirement is alleviated for the AMC at the physical layer. Numerical results demonstrate that the proposed AMC-HARQ design outperforms either application of AMC only at the physical layer or incorporation of ARQ with fixed modulation and coding scheme.